The influence of code-check first, online customer reviews and free shipping on the decision to purchase fashion products for Budi Darma University students in shopee market place - Anda Yanny; Mela Novaliska Panjaitan; Ronda Deli Sianturi (Trigin Publisher, 2023)
One of Shopee's newest programs is COD-Check First, which provides purchasing decisions in the sense of maintaining consumer trust. Regarding the quality of products and services, Shopee also provides a column for reviews or comments from consumers who have used this service. This is also to ensure consumer comfort and consumer confidence in continuing to use this online shop. Shopee also always produces programs that please consumers, such as free shipping. The results of research using SPSS 20 with 100 respondents who came from students at Budi Darma University showed that COD-Check first had no effect on purchasing decisions for Gen Z. Free shipping and customer reviews are what can influence purchasing decisions. The more free shipping and the better the consumer's rating, the higher the decision to purchase fashion products